PENERAPAN TEORI KOMUNIKASI DALAM KEHIDUPAN BERORGANISASI DI UNIVERSITAS SRIWIJAYA - Fathiya Cinindyta Utari (Journal of Dialogos, 2024)
This article explores communication in an organizational context, emphasizing the reciprocal nature of communication processes that affect organizational members in a mutually influential manner. By exploring the application of communication theory in organizations, this article details how communicators can create perceptual changes that support the cooperation and interdependence of organizational members. In order to answer the main question posed, this article formulates several questions related to the definition of theory, communication, and communication theory, the benefits of understanding communication theory, as well as the application of communication theory in the context of organizations at Sriwijaya University. The purpose of this article is to provide an in-depth understanding of these concepts and apply them in the context of organizational life in an academic environment.